Pilates method in quality of life, emotional overloading and stress of caregivers of autistic children (Research, Society and Development, 2022)
Objectives: To evaluate the effect of the Pilates Method on quality of life, emotional overload and stress in babies with Autism Spectrum Disorder. Methods: The present research is a randomized controlled clinical trial and the Short Form Health Survey (SF-36),questionnaire was used to assess the quality of life, the perceived stress scale for stress and for the emotional overload the questionnaire to assess the physical, emotional and social impact of the role of informal caregiver. Results: It was possible to notice the relationship of the variables researched with the level of stress, quality of life and emotional overload and the effect of pilates on them. Results: It was possible to notice the relationship of the variables researched with the level of stress, quality of life and emotional overload and the effect of Pilates on them. Conclusion: It was concluded that the Pilates Method proved to be a modality of physical exercises, with effectiveness in improving emotional overload, stress levels and quality of life in caregivers of autistic children.